Dermoscopy of Non-Melanocytic Skin Tumors: A Descriptive Study in a Tertiary Care Hospital - Deeptara Pathak Thapa; Sajana Bhandari; Harihar Adhikari; Sammi Joshi (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: Dermoscopy is a non-invasive technique that enhances visualization of morphological lesions invisible to naked eye examination and aids in clinical diagnosis. We study its role in non-melanocytic skin tumors.